Analisis Potensi Likuifaksi Berdasarkan Data Cone Penetration Test Dengan Metode Olsen (Studi Kasus: Gedung Kejaksaan Tinggi Riau) - Annisa Soraya Hasibuan; Muhamad Yusa; Agus Ika Putra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Liquefation is an occurrence triggered by the earthquake that can cause fatal damage. When the earthquake occurs, the soil on location changes in nature from solid to liquid due to massive cyclic load. One of the liquefaction analysis methods is based on the results of the Cone Penetration Test (CPT). In general the analysis is based on the results of electrical CPT (CPTe), however, in Indonesia, it is preferent by using mechanical CPT data (CPTm). This study aims to compare the results of liquefaction analysis namely the Liquefaction Potential Index (LPI) using the Olsen method based on the value of mechanical CPT and converted mechanical CPT. This study is located on the Kejaksaaan Tinggi Riau Building. Based on the results study, that research site has a higher liquefaction potential if analyzed using CPTm data that has been corrected to CPTe. The range of LPIm value compared to LPIe is 0,373 – 0,638 with the category of liquefaction potential “Moderate” to “Very High”. Keywords: Liquefaction, Olsen Method, mechanical sondir, electrical sondir.